THE STUDY OF COGNITIVE STRATEGIES IN LEARNING SPEAKING USED BY THE THIRD SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT ALAUDDIN STATE ISLAMIC UNIVERSITY - Rahmawati S; Erwin Akib; Ilmiah (FKIP Unismuh Makassar, 2021)
This research method is descriptive qualitative. In compiling the data, the researcher conducted interviews and observations. In this study, 42 third-semester students of the Department of English Education at the Alauddin State Islamic University in Makassar were the research subjects. In addition, four students were interviewed, and 42 students were observed during the speaking class.The results showed that: 1) There are several classifications of cognitive strategies used by students in learning to speak, namely practicing, receiving and sending messages, analyzing and reasoning, and structuring input and output. In practice, students use repetition, apply rules of pronunciation, rules of grammar are too seldom used. Then, during receiving and sending messages, students need to think for a moment before giving their ideas. Next during receiving and sending messages, students need to think for a minute before providing their idea. Furthermore, while the strategy of analyzing and reasoning, students apply to analyze expressions, translating, and contrasting what they learn. The final cognitive strategy is to create structures for input and output. Students usually get notes and shorten the material. 2) Cognitive strategies have a positive effect on students' speaking performance